2009
DOI: 10.1016/j.bbrc.2009.02.082
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics reveal a concerted upregulation of methionine metabolic pathway enzymes, and downregulation of carbonic anhydrase-III, in betaine supplemented ethanol-fed rats

Abstract: We employed a proteomic profiling strategy to examine the effects of ethanol and betaine diet supplementation on major liver protein level changes. Male Wistar rats were fed control, ethanol or betaine supplemented diets for 4 weeks. Livers were removed and liver cytosolic proteins resolved by one-dimensional and two-dimensional separation techniques. Significant upregulation of betaine homocysteine methyltransferase-1, methionine adenosyl transferase-1, and glycine N-methyltransferase were the most visually p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
36
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 29 publications
(15 reference statements)
3
36
0
Order By: Relevance
“…Ca3 is considered as one of the proteins involved in oxidative stress response both in liver and skeletal muscle [20]. However, it has also been reported as the worst catalyst for CO 2 hydration as compared to other isozymes [22]. We found Ca3 to be differentially upregulated in rats fed the HFSD.…”
Section: Discussionsupporting
confidence: 57%
“…Ca3 is considered as one of the proteins involved in oxidative stress response both in liver and skeletal muscle [20]. However, it has also been reported as the worst catalyst for CO 2 hydration as compared to other isozymes [22]. We found Ca3 to be differentially upregulated in rats fed the HFSD.…”
Section: Discussionsupporting
confidence: 57%
“…A SAM-dependent increase in CDH may have the desired consequence of increased betaine formation needed for remethylation of homocysteine to methionine, thereby blunting the toxicity of homocysteine to induce ER stress (25). Data from this study and others (30,54) show that SAM or betaine treatments have the ability to attenuate many of the damaging effects of ethanol on the liver through modulation of key enzymes involved in methionine metabolism.…”
Section: Discussionmentioning
confidence: 65%
“…Recent proteomic data show that a betaine-supplemented ethanol diet preserves functionality of several key cytosolic enzymes of methionine metabolism including betaine homocysteine methyltransferase (BHMT) and methionine adenosyltransferase (30). Data presented herein also shows ethanol-and SAM-dependent alterations in the levels of mitochondrial proteins interconnected with methionine metabolism via choline and glycine metabolism; CDH, DMGDH, and SARDH.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Adenosylhomocysteinase converts SAH to Hcy, which is re-methylated by 5-methyltetrahydrofolate back to methionine. It is reported that changes in the SAM/SAH ratio affected liver PIMT activity in rats after betaine administration (Kharbanda et al 2007(Kharbanda et al , 2009Ghandour et al 2002;Carter and Aswad 2008). Moreover, SAH is a potent inhibitor of many methyltransferases including PIMT.…”
Section: Discussionmentioning
confidence: 99%